Serum levels of interleukin-2 predict the recurrence of atrial fibrillation after pulmonary vein ablation. Issue 1 (May 2015) - Cabrera-Bueno, Fernando; Medina-Palomo, Carmen; Ruiz-Salas, Amalio; Flores, Ana; Rodríguez-Losada, Noela; Barrera, Alberto; Jiménez-Navarro, Manuel; Alzueta, Javier
Highlights Levels of interleukin-2 are associated with the recurrence of atrial fibrillation. There are potential association between IL-2 and the results of catheter ablation. It is possible an inflammatory substrate in the recurrence of atrial fibrillation.